Access to information as an ethical value in knowledge organization: dialogues between scientific literature and normative sources in the Brazilian perspective - Evangelista, Isadora Victorino [UNESP]; Gardini Santos, Joao Carlos [UNESP]; Chaves Guimaraes, Jose Augusto [UNESP]; Fernandez-Molina, Juan Carlos (Univ Brasilia, Dept Ciencia Informacao, 2020)
Information access in a fast, transparent and accurate way is one of the main objectives of information units, implying an ethical dimension that makes this objective identified as a moral value in the activities of Knowledge Organization. This issue becomes even more evident when considering the Brazilian Law of Information Access (LAI), which, among other purposes, regulates the fundamental right of information access, which is constitutionally present. As main goal, the present article sought to relate the text of said law and the moral aspects found in the literature of the area of Ethics in Organization of Knowledge. Methodologically, the LAI integral text and a corpus of thirteen articles that worked with the ethical dimension in the studies on Knowledge Organization were comparatively analyzed, in order to identify the moral aspects found in this normative and bibliographic group. In conclusion, it is possible to identify a link between the analyzed scientific literature and normative prediction in Brazil, so that information Access as a moral supravalue that aims at equanimity and quality access to knowledge produced by society, and the normative about such access in terms of transparency in a democratic society dialogue in a consonant manner.
Keywords: information access; Ethics; Information Science; law of information access